Implementation of Health Protocol on Nursing Students in The Dormitory During Pandemic - Simamora, Marya Listiana; Purba, Tuti Melinda Anggreini; Leonardo, Jose; Watania, Lani Natalia; Diannita, Catharina Guinda (Journal of Nursing Science Update (JNSU), 2023)
Global prevalence data released by WHO (2021) shows a decrease in positive cases of COVID-19 in Indonesia by 18%. One of the government's policy efforts to prevent the spread of the COVID-19 virus is establishing health protocols, including physical distancing, wearing masks, and hand washing. There is an increase in the number of dormitory residents at one of the western Indonesian universities, which causes a decrease in the effectiveness of implementing health protocols. The study aims to identify the application of health protocols, including physical distancing, wearing masks, and hand washing among nursing students. This study uses descriptive quantitative research methods. The instrument used is an online questionnaire, a random sampling technique with univariate data. The results showed that the 2019 and 2020 nursing students, 232 respondents (99.1%) and two respondents (0.9%) did not apply health protocols properly. In conclusion, most nursing students in Western Indonesian universities applied health protocols. Suggestions for students are expected to be able to maintain and improve the implementation of health protocols in dormitories to prevent the increase in the spread of COVID-19 or other infections. For further research, we are expected to use bivariate analysis to suppress the increase in respiratory infection cases.